2021
DOI: 10.1016/j.bpa.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 impact on the renal system: Pathophysiology and clinical outcomes

Abstract: COVID-19 has numerous deleterious effects throughout the body. Prior studies had shown that the incidence of acute kidney injury in COVID-19 patients could be as high as 25%. There are also autopsy reports showing evidence of viral tropism to the renal system. In this regard, COVID-19 can damage the kidneys and increase a patient's risk of requiring dialysis. Available evidence suggests that renal involvement in COVID-19 infection is not uncommon, and there has been an increased incidence of chronic kidney dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
2
12
0
1
Order By: Relevance
“…Histological postmortem findings have revealed that COVID‐19 patients have endothelial damage in several extrapulmonary vascular beds, including the renal microcirculation (5,40). This renal endothelial injury, consequently, may result in impaired control of renal arteriolar tone, especially by reducing the bioavailability of nitric oxide, which favors a state of sustained vasoconstriction and leads to hypoperfusion and prerenal azotemia (7). Up to now, in addition to evidence from postmortem analyses, few studies, to our knowledge, have verified the relationship between endothelial damage and renal dysfunction in COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological postmortem findings have revealed that COVID‐19 patients have endothelial damage in several extrapulmonary vascular beds, including the renal microcirculation (5,40). This renal endothelial injury, consequently, may result in impaired control of renal arteriolar tone, especially by reducing the bioavailability of nitric oxide, which favors a state of sustained vasoconstriction and leads to hypoperfusion and prerenal azotemia (7). Up to now, in addition to evidence from postmortem analyses, few studies, to our knowledge, have verified the relationship between endothelial damage and renal dysfunction in COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…As consequence, a dysfunctional endothelium has a negative impact on the control of hemostasis, fibrinolysis, vasomotion, inflammation, and vascular permeability (4). These conditions are also determinants for many complications of severe COVID‐19, such as cardiovascular events (6), kidney injury (7), acute respiratory distress syndrome (8), and coagulation abnormalities (9).…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, beyond 5.5 million cases and 120,880 deaths due to COVID-19 are officially reported until the date. COVID-19 is mainly pneumonia characterized by cough, a fever, shortness of breath, fatigue, and gastrointestinal symptoms such as anorexia, nausea, vomiting, and diarrhea [ 2 ]; however, all organs could be affected by the virus, including the endocrine [ 3 ], cardiovascular [ 4 ], renal [ 5 ] and nervous systems [ 6 ] regardless the presence of pneumonia. SARS-CoV-2 is transmitted from human to human by many mechanisms such as respiratory droplets, aerosols, and unprotected contact [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study showed that proteinuria and hematuria increased the chances of admission to the intensive care unit (ICU) and the severity of the disease in COVID-19 patients. Old age and underlying diseases such as hypertension, diabetes, and heart diseases are the risk factors for acute kidney damage (22,23).…”
Section: Effect Of Covid-19 On Different Systems In the Bodymentioning
confidence: 99%